EFFECT OF NONI FRUIT (Morinda citrifolia) POWDER AS FEED ADDITIVE ON INTESTINAL MICROFLORA AND VILI CHARACTERISTICS OF HYBRID DUCK - David Kurniawan; Eko Widodo; Irfan H Djunaidi (Buletin Peternakan, 2016)
Noni fruit is a medicanal plant with biological activity like antimicrobial and antioxidant that could potentially be used as a feed additive in poultry. This research investigated the effect of noni fruit powder as feed additive on intestinal microflora and villi characteristics of hybrid duck. The subjects for this study were one hundred fifty of 2-week-old hybrid duck that were divided into 5 dietary groups, namely P0: basal feed serving as negative control, P1: basal feed + 1 % noni fruit powder, P2: basal feed + 2 % noni fruit powder, P3: basal feed + 3 % noni fruit powder, P4: basal feed supplemented with tetracycline antibiotic (300mg/kg feed) as positive control. Data were analyzed by one-way of Completely Randomized Design and if there was significant effect followed by Duncan’s Multiple Range Test. The result show that levels of noni fruit powder significantly influence (P<0.01) intestinal microflora. Total Escherichia coli of intestinal microflora was decreasing, however total Lactic acid bacteria was equal to negative control. Intestinal villi characteristics show that significantly different (P<0.01) with used noni fruit powder. Treatment noni fruit powder 1% can increase villus length and villus surface area. (Key words: Duck, Intestinal changes, Noni Fruit, Phytobiotic)